Specimen Orientation by Marking the Peripheral End: (Potential) Clinical Advantages in Prostate Biopsy. (27th July 2011) - Galosi, Andrea Benedetto; Muzzonigro, Giovanni; Lacetera, Vito; Mazzucchelli, Roberta
Abstract : The aim of this paper is to identify advantages that could be obtained by orientation of the biopsy specimen using the marking technique. We reviewed our experience (4, 500 cases) and the published literature. The peripheral (proximal) end of the fresh specimen is marked with ink soon after needle delivering in a few minutes. It is performed easily in association with pre-embedding method. Five potential clinical advantages were identified: (1) tumor localization, (2) atypical lesions localization and planning rebiopsy strategy, (3) planning surgical strategy, (4) selection criteria for focal therapy and active surveillance, and (5) cost reduction. Peripheral end marking is low cost, easy and reproducible. It drives several potential advantages in cancer diagnosis or isolated atypical lesions, in particular, spatial localization within the biopsy (transition versus peripheral zone, anterior versus posterior, subcapsular versus intraparenchima, and extraprostatic extension) should be easy and reliable. We can add a new pathological parameter: pathological orientation or biopsy polarity.